2016
DOI: 10.1080/03007995.2016.1218833
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of renal artery stent combined with optimal medical therapy in patients with severe atherosclerotic renal artery stenosis

Abstract: Renal artery stent combined with optimal medical therapy as a treatment has a beneficial effect on blood pressure control and estimated glomerular filtration rate in selected patients with atherosclerotic renal artery stenosis. Larger studies with a longer follow-up appear necessary to further confirm these intriguing findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…Indications for endovascular therapy was defined as RAS ≥70% and Grade 3 hypertension without antihypertensive drugs, or systolic and diastolic pressures greater than 140 or 90 mmHg after treatment with triple antihypertensive drug therapy. The exclusion criteria for PTA with stent implantation were as follows: (a) intolerance to heparin or antiplatelet drugs, (b) renal artery dissection, (c) severe renal insufficiency (glomerular infiltration rate < 30 ml/min), (d) allergy to iodinated contrast agent, or (e) life expectancy <2 years. Consent was obtained from all individual participants included in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indications for endovascular therapy was defined as RAS ≥70% and Grade 3 hypertension without antihypertensive drugs, or systolic and diastolic pressures greater than 140 or 90 mmHg after treatment with triple antihypertensive drug therapy. The exclusion criteria for PTA with stent implantation were as follows: (a) intolerance to heparin or antiplatelet drugs, (b) renal artery dissection, (c) severe renal insufficiency (glomerular infiltration rate < 30 ml/min), (d) allergy to iodinated contrast agent, or (e) life expectancy <2 years. Consent was obtained from all individual participants included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Because histopathology was rarely available, the diagnosis was made based on angiographic imaging, including selective angiography or computed tomographic (CT) angiography. By analyzing the angiographic findings for the renal artery, stenosis was classified into three types: multifocal (multiple stenosis or string‐of‐beads appearance), unifocal (stenosis <1 cm in length), and tubular (stenosis ≥1 cm in length).…”
Section: Methodsmentioning
confidence: 99%
“…34 Even larger BP reductions by an average of 20 mm Hg were also reported in uncontrolled studies. 35,36 However, these findings were not confirmed in four meta-analyses of randomized controlled trials 37-40 and a recent systematic review. 41 In addition, benefits seen in some studies may be more pronounced if appropriate subgroups were to be identified.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding RVH, the majority of three retrospective and nine prospective cohort studies included in a recent meta‐analysis reported a decrease of BP after PRR, with the mean BP falling by approximately 10 mm Hg . Even larger BP reductions by an average of 20 mm Hg were also reported in uncontrolled studies . However, these findings were not confirmed in four meta‐analyses of randomized controlled trials and a recent systematic review .…”
Section: Discussionmentioning
confidence: 99%
“…Stent implantation is a treatment for renovascular hypertension due to atherosclerotic renal artery stenosis 1 . Renal artery intramural haematoma (IMH) is a rare complication after renal artery stenting 2 .…”
Section: Introductionmentioning
confidence: 99%